Comparison of fertilization, hatching, and survival rates in induced triploid hybrid catfish (Clarias gariepinus) X Clarias macrocephalus produced by heatshock. - Catigan, Christine Palangre
Catfishes are important source of relatively cheap animal protein. Its culture is growing rapidly and is faced with many problems. Clarias macrocephalus or the native 'pantat' is the one that is favored by many for its succulent and delicious meat. Its slow growth led the introduction of the African variety, Clarias gariepinus that is larger in size and of rapid growth. This has led to the decline of the native 'pantat'., The hybridization of these two species proves to be a potential solution to the disappearance of the native catfish. The production of a hybrid with good meat quality and rapid growth is combined with triploidization to increase body size. It has produced sterile catfishes of larger marketable size. Triploidization is employed by heatshocks to temperatures of 35 degrees centigrade, 37 degrees centigrade, and 39 degrees centigrade. Parameters of fertilization, hatching, and survival rates were obtained to as basis for determining the temperature that is best suited for triploidization. Temperature of 35 degrees centigrade was found to be most effective because it produces high viability in fertilization, hatching, and survival of the produced hybrid. Though it is significantly lower (a=0.05) than the control, it has obtained higher values compared to those exposed to temperatures of 37 degrees centigrade and 39 degrees centigrade.